Theory of functional grammar : Origin and evolution. - Al-Fawal, Mohammad; Rkhamya, Knadeja (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
this research gives notice about the concept of theory of functional grammar and the most important developments in it since its inception to the present time, then standing on its roots in the heritage of the Arab, refers to the famously of scientists whom have called for ridding the Arabic grammar, which suspended its ramifications overwhelmed and hamper his gift, such as Al_jahiz which claimed the calls in one of his letters to the limitation in the instruction as to the boy on the core issues that lead to the safety of obscene melody, and the amount of the ignorance of the common folk in the book that he wrote, and felt that chant, and something that he described. Search moves then to talk about the principles and objectives as functional theory, And it ends with a summary showing its importance, and calls for the need to apply its principles in the field of education.